THE SPECIFICS OF THE SELF-CONCEPT OF ADOLESCENTS WITH DISABILITIES - Tikhonova I. V., I. V.; Khazova , S. A. (Modern Psychology, 2019)
The article presents the results of a methodological analysis and a comparative empirical study of the self-concept of adolescents with disabilities. The study involved 24 adolescents with visual impairment, 29 adolescents with mental retardation, 37 adolescents with severe speech disorders, 19 adolescents with impaired hearing. To study the self-concept of adolescents, the method of A. M. Prikhozhan was used. All respondents have a rather positive view of themselves as individuals. Adolescents with hearing and speech impairments are distinguished by maximum self-confidence, are satisfied with life circumstances, they highly value their appearance, consider their behavior to be correct and socially approved. Respondents with a deficit of visual functions and mental retardation have more realistic ideas about themselves, critically evaluate their behavior. When development is delayed, there is the least satisfaction with their position in the family. The conclusion is made about the dependence of the realism and maturity of the self-concept not only on the specifics of the violation, but also on the inclusion of adolescents with disabilities in the educational environment.
Keywords: self – concept, identity, self-satisfaction, disabilities, teenagers' with disabilities